PENERAPAN METODE PEMBERIAN TUGAS UNTUK MENINGKATKAN KEMAMPUAN MEMBACA NYARING SISWA KELAS IV SD NEGERI 013 PAGARAN TAPAH DARUSSALAM - Kelana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the low ability of fourth-grade students at SD Negeri 013 Pagaran Tapah Darussalam in reading aloud. The study aims to improve students’ oral reading skills through the assignment method. The subjects of the study were 20 fourth-grade students, consisting of 10 female and 10 male students in the 2014–2015 academic year. This research employed a classroom action research design. The research instruments consisted of performance assessment instruments and data collection sheets in the form of teacher and student activity observation sheets. Based on the results, students’ oral reading skills improved across cycles. Preliminary data showed an average score of 63.2, with only 19.2% of students (5 students) achieving the minimum mastery criterion (KKM) score of 70. After applying the assignment method in the first cycle, the average score increased to 68.9, with 50% of students (13 students) meeting the KKM. In the second cycle, the average score rose to 81.4, achieving 100% mastery. Thus, the implementation of the assignment method is considered successful in improving students’ ability to read aloud.